Mastering research methods - Chua, Y.P. (Mcgraw-Hill Education, 2012)
This book is a practical guide for those who are directly involved in research. It covers all aspects of research methodology and is a useful teaching and learning tool for courses related to research at both undergraduate and postgraduate levels. This book can also be used as a reference by researchers when they are conducting and reporting their research. Not only does Mastering Research Methods introduce readers to methods of conducting research, it helps them to easily understand the entire research process. In addition, explanations about the concept of research, especially the design, measurement and sampling procedures, and format of research reports are simplified to help readers of all levels better understand what they are reading. Concepts are explained in detail with examples to enable readers to carry out confidently each stage of the research process. Exercises are provided at the end of each chapter to help readers reinforce their understanding of the topics covered in the chapter.